2004
DOI: 10.1002/rra.749
|View full text |Cite
|
Sign up to set email alerts
|

Modelling effects of discharge on habitat quality and dispersal of juvenile humpback chub (Gila cypha) in the Colorado River, Grand Canyon

Abstract: A two-dimensional hydrodynamic model was applied to seven study reaches in the Colorado River within Grand Canyon to examine how operation of Glen Canyon Dam has affected availability of suitable shoreline habitat and dispersal of juvenile humpback chub (Gila cypha). Suitable shoreline habitat typically declined with increasing discharges above 226-425 m 3 / s, although the response varied among modelled reaches and was strongly dependent on local morphology. The area of suitable shoreline habitat over cover t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 30 publications
1
30
0
Order By: Relevance
“…Apparently, the underlying capacities are likewise executed in the wild (e.g., a large river). In agreement with our study, dispersal simulations in the Colorado River also demonstrated that low swimming performances of young fish can result in high deviations from passive diffusion models (Korman et al 2004).…”
Section: Developmental Stagesupporting
confidence: 91%
See 1 more Smart Citation
“…Apparently, the underlying capacities are likewise executed in the wild (e.g., a large river). In agreement with our study, dispersal simulations in the Colorado River also demonstrated that low swimming performances of young fish can result in high deviations from passive diffusion models (Korman et al 2004).…”
Section: Developmental Stagesupporting
confidence: 91%
“…The first possibility, that larvae were washed downstream passively during high flow, could be because a rise in river discharge often involves a decline of current-reduced inshore habitats (Korman et al 2004), which are preferably used by young nase (Keckeis et al 1997), and if such refuges are scarce, strong currents during elevated discharge (Fig. 3) may induce extensive washouts of 0+ fish communities (Harvey 1987;Bischoff and Wolter 2001).…”
Section: Dischargementioning
confidence: 99%
“…While modelling provides an opportunity to test a variety of scenarios not possible in the field, the challenge is developing a robust result that accounts for the multitude of environmental variables that act in concert or independently to affect fish behaviour in a dynamic flowing environment. Links between various numerical models and population parameters such as abundance, growth, survival or recruitment have not been well documented (Korman et al, 2004).…”
Section: Summary Of Research Methodologiesmentioning
confidence: 99%
“…Dispersal modes of fish during the crucial larval phase of their life cycle is an important factor in recruitment and is governed by abiotic triggers (e.g., hydrology and hydraulics: Pavlov (1994); and discharge: Lechner et al 2017;Korman et al (2004); Reichard and Jurajda (2004)), in combination with biotic triggers (e.g., physiology and behaviour: Gaudin and Sempeski (2001); Heggenes and Dokk (2001);Pavlov (1994)). In a study on juvenile fish movement, Pavlov et al (2008) concluded that micro-scale habitat heterogeneity, interacting with individual behavioural variability within fish populations, could affect the proportion of resident to migratory fish in a river.…”
Section: Introductionmentioning
confidence: 99%
“…Relating to reef sounds, Staaterman et al (2012) linked the navigation approach from Codling et al (2004) with a three-dimensional (3D), coupled biophysical model (Paris et al 2013) and found higher settlement rates for oriented larvae. Models of larval fish dispersal patterns within riverine ecosystems are rare (e.g., Wolter and Sukhodolov 2008;Korman et al 2004;Cowan et al 1993). However, models that include rheoreaction have been developed for several organisms and their larval developmental stages (Marcos et al 2012;Mork et al 2012;Booker et al 2008).…”
Section: Introductionmentioning
confidence: 99%